11-7m=-52

Simple and best practice solution for 11-7m=-52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-7m=-52 equation:


Simplifying
11 + -7m = -52

Solving
11 + -7m = -52

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -7m = -52 + -11

Combine like terms: 11 + -11 = 0
0 + -7m = -52 + -11
-7m = -52 + -11

Combine like terms: -52 + -11 = -63
-7m = -63

Divide each side by '-7'.
m = 9

Simplifying
m = 9

See similar equations:

| 44-[4+8y-2(y+2)]=-4(3y-7)-[9(y-1)-12+20] | | -11+x-5-3=7x-7 | | 3+4x=-37 | | d+3/4=2 | | -14x=8 | | d+3/4=4 | | 4d+3/4=4 | | 27=70n | | g=-8-7 | | 3x^2-9x-120=0 | | -5+9+6= | | 4b-8-b=10b | | (2x-5)(3x+2)= | | 12x+6=-6 | | 4x+4=x+3 | | z-m=z+bz | | -7(2x-13)=3(-2x+9) | | -7(2x-13)=3(-2x+9) | | f(a)=-2a^2+1 | | 4s+13=7s+34/4 | | -5+2(8+8p)=43 | | -2/9m-4=7/18 | | 40=16+5(2t-3) | | 420*7/6=n | | (N/3)=2 | | -x^2+36x-62=0 | | 7(1+8k)=-49 | | 7(b+3)=7(b)-21 | | -4a^5(6a^5)= | | -4(d+1)-d-9=-5(d+4)+7 | | 3(y-5)/2=5 | | 7(b+3)=7b-21 |

Equations solver categories